PENGARUH FINANCIAL DISTRESS, KOMPLEKSITAS OPERASI, DAN PERSENTASE KEPEMILIKAN INSTITUSIONAL TERHADAP AUDIT DELAY (Studi Empiris Pada Perusahaan Sektor Perdagangan, Jasa, dan Investasi Yang Terdaftar Pada Bursa Efek Indonesia Periode 2018-2020) - Hani Arlina Putri (2022)
Public entities are obligated to publish their annual report and financial statement to the regulators. The published financial statement is the report that has been audited by independent auditors. The length of audit's process could affect the publication date. This research aimed to examine the effect of financial distress, operation complexity, and institutional ownership toward audit delay. The research uses secondary data by using annual reports or financial statements published by Otoritas Jasa Keuangan (OJK) and/or company official website. Population in this research are entity listed on trade, service, and investment sector at Indonesian Stock Exchange (IDX) period 2018-2020 and obtained 168 entity. By using purposive sampling method, this research obtained 275 samples. Data were analyzed using multiple linear regression panel data, classical assumption test, and hypothesis test with software STATA v.12.1. Result of the study by using 0,05 signification shows that financial distress and operation complexity have positif impact toward audit delay, meanwhile institutional ownership does not have any effect toward audit delay. Keywords: Audit Delay, Financial Distress, Operation Complexity, and Institutional Ownership